Planning the Ideal Refugee Camp? A Critical Interrogation of Recent Planning Innovations in Jordan and Germany - Dalal, Ayham; Darweesh, Amer; Misselwitz, Philipp; Steigemann, Anna (Urban planning, 2018)
With the increase of refugee movements since 2014 in Europe and the Near East, the debate of how to plan appropriate shelters and emergency accommodation has gained a new momentum. Established techno-managerial approaches have been criticised as inappropriate and the professional community of planners and architects was increasingly drawn into debates for alternative solutions. This article traces the “innovations” that promise better, more effective, and more humane emergency shelters using the examples of the “Tempohomes” in Berlin as well as the Jordanian refugee camps of Zaatari and Azraq. In both cases, planners were employed to address the ambivalent reality of protracted refugee camps and include “lessons” from failures of earlier solutions. While the article acknowledges the genuine attempt of planners to engage with the more complex needs and expectations of refugees, a careful look at the results of the planning for better camps reveals ambivalent outcomes. As camps acquire a new visual appearance, closer to housing, which mixes shelter design with social spaces and services as essential parts of the camp; these “innovations” bear the danger of paternalistic planning and aestheticisation, camouflaging control under what seems to be well-intended and sensitive planning. The article focuses on refugees’ agency expressed in critical camp studies to interrogate the planning results. While recent critical refugee studies have demanded recognition of refugees as urban actors which should be included in the co-production of the spatial reality of refugee accommodations, new planning approaches tend to result in a shrinking of spaces of self-determination and self-provisioning of refugees.